Discrete Carleman estimates and three balls inequalities - Fernández-Bertolin, Aingeru; Roncal, Luz; Rüland, Angkana; Stan, Diana (Calculus of variations and partial differential equations, 2021)
We prove logarithmic convexity estimates and three balls inequalities for discrete magnetic Schrödinger operators. These quantitatively connect the discrete setting in which the unique continuation property fails and the continuum setting in which the unique continuation property is known to hold under suitable regularity assumptions. As a key auxiliary result which might be of independent interest we present a Carleman estimate for these discrete operators.
Gesehen am 30.12.2021